4 - China in Africa with New Approach of Media Development - Memon, Najamul Saqib; Sandano, Imran Ali (Africa Development, 2024)
Mass media has not only changed the mode of information-sharing but has also changed the mode of policy, foreign policy-making and people-to- people contact in being used as a means of soft power. This paper focuses on Chinese investment in the media sector of African countries and explores what motivates China’s huge investments in the African media landscape. The study is descriptive, based on primary and secondary sources of literature. Methodologically, it uses qualitative research through content analysis of ‘soft power politics’ and ‘public diplomacy’ theories. China’s media development assistance in Africa is a manifestation of the Chinese strategy of soft power politics and the application of public diplomacy. This study claims that China’s media development assistance programme is helping Africa to develop its media infrastructure, techniques of broadcasting and cultural exchanges, which influence African public opinion and offer media content that is entirely different from Western-dominated media groups. In return, this helps China to promote a positive image and win the hearts and minds of people on the African continent.